The organisational structure of the economic security service of the enterprise and the main functions of its divisions - A. N. Shchapov (Вестник университета)
In order to make science-based decisions related to business security by the owners and management of the enterprise, the following tasks are solved in the article: the organisational structure of the economic security service of the enterprise, as well as the main functions of its divisions, are developed. The relevance of solving these problems is primarily due to the low efficiency of law enforcement agencies in protecting property rights and economic interests of domestic entrepreneurs. The scientific novelty of the study lies in the development of a basic, universal organisational structure of the economic security service of a modern enterprise. Starting from the goal of creating an economic security service, using a systematic and risk-oriented approach, its tasks have been collected, defined and comprehensively analyzed. Taking into account the increased complexity and confidentiality of tasks, based on the structural and functional approach, the functions of the economic security service of the enterprise were formulated, which were structured and distributed to specific departments. Elements of scientific novelty are also the recognition of the existence of intelligence units of the economic security service of enterprises operating in violation of the law, as well as an analysis of their functions in order to develop the organisational structure of counterintelligence units.